2023
DOI: 10.1007/s00248-023-02198-7
|View full text |Cite
|
Sign up to set email alerts
|

Two Complete Genomes of Male-Killing Wolbachia Infecting Ostrinia Moth Species Illuminate Their Evolutionary Dynamics and Association with Hosts

Abstract: Wolbachia is an extremely widespread intracellular symbiont which causes reproductive manipulation on various arthropod hosts. Male progenies are killed in Wolbachia-infected lineages of the Japanese Ostrinia moth population. While the mechanism of male killing and the evolutionary interaction between host and symbiont are significant concerns for this system, the absence of Wolbachia genomic information has limited approaches to these issues. We determined the complete genome sequences of wFur and wSca, the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
(118 reference statements)
1
4
0
Order By: Relevance
“…The presence of the irregular GC skew in wFI, meant that there was no obvious GC skew to identify a possible origin of replication, which also suggested that wFI may have undergone frequent rearrangements. This abnormal GC skew pattern has also been observed in other Wolbachia genomes [35][36][37][38][39]. However, it has been observed that Wolbachia with reduced genomes exhibit a strong GC skew [40].…”
Section: Assembly and Annotationsupporting
confidence: 60%
“…The presence of the irregular GC skew in wFI, meant that there was no obvious GC skew to identify a possible origin of replication, which also suggested that wFI may have undergone frequent rearrangements. This abnormal GC skew pattern has also been observed in other Wolbachia genomes [35][36][37][38][39]. However, it has been observed that Wolbachia with reduced genomes exhibit a strong GC skew [40].…”
Section: Assembly and Annotationsupporting
confidence: 60%
“…wSca] and Ec-Oscar [wCauA]) and Type II Oscar (Hm-Oscar [wHm-t] and Em/Eh-Oscar [wFem]; Figure 2C). Whereas Oscar in the newly sequenced wSca strain was not identical to that in the previously sequenced wSca strain (43), it exhibited high homology to Oscar proteins in the previously sequenced wSca (similarity: 90.4% in 1797 amino acids; bit score: 3241, BLASTp) and wFur (similarity: 94.2% in 1830 amino acids; bit score: 3432) (Table S1). Intriguingly, the Type II Oscar homologs Hm-Oscar and Em-Oscar exhibited higher homology than the wSca strains (similarity: 98.5% in 1181 amino acids; bit score: 2362).…”
Section: Phylogenetic Analysis Classified the Oscar Proteins Into Two...mentioning
confidence: 90%
“…For example, the MK Wolbachia strain, w Hm-t, is thought to have evolved from its closely related non-MK strain, w Hm-c, in the tea tortrix, Homona magnanima , by acquiring an MK-associated prophage region [ 18 ]. By contrast, Ostrinia furnacalis and Ostrinia scapulalis harbour closely related MK Wolbachia strains that show an extremely high degree of genomic similarity to several inversions [ 19 ]. The MK Wolbachia strains in Ostrinia moths are thought to have descended from their common ancestral hosts and have maintained a stable genome structure throughout their evolution [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Ostrinia furnacalis and Ostrinia scapulalis harbour closely related MK Wolbachia strains that show an extremely high degree of genomic similarity to several inversions [ 19 ]. The MK Wolbachia strains in Ostrinia moths are thought to have descended from their common ancestral hosts and have maintained a stable genome structure throughout their evolution [ 19 ]. In the highly host-dependent symbiotic bacterium, Wolbachia , substantial changes in the genome structure can disrupt phenotypic expression and intergenic interactions, posing major risks to Wolbachia fitness.…”
Section: Introductionmentioning
confidence: 99%